Total and Differential White Blood Cell Counts in Late Life Predict 8‐Year Incident Stroke: The Honolulu Heart Program. Issue 3 (4th March 2015) - Huh, Ji Young; Ross, George Webster; Chen, Randi; Abbott, Robert D.; Bell, Christina; Willcox, Bradley; Launer, Lenore; Petrovitch, Helen; Kaya, Brock; Masaki, Kamal
Abstract : Objectives: To study the association between total and differential white blood cell (WBC) count and incident stroke in an older Asian population. Design: Prospective population‐based study with 8 years of follow‐up. Setting: The Honolulu Heart Program, Oahu, Hawaii. Participants: Japanese‐American men aged 71 to 93 who were free of stroke and had baseline WBC counts measured in 1991–93 (N = 3, 342). Measurements: Participants were divided into quartiles of total and differential WBC count for analysis and were followed for incident stroke (thromboembolic and hemorrhagic (hemorrhagic)) for 8 years using data from a comprehensive hospital surveillance system. Results: Age‐adjusted incident stroke rates increased significantly with increasing WBC quartile (Q1, 7.68; Q2, 9.04; Q3, 9.26; Q4, 14.10 per 1, 000 person‐years of follow‐up, P = .001). Hazard ratios (HRs) for stroke for each quartile of total and differential WBC count were obtained using Cox regression analysis, with the lowest quartile as the reference group. After full adjustment, including age; cardiovascular risk factors; fibrinogen; prevalent coronary heart disease, cancer, or chronic obstructive pulmonary disease, and nonsteroidal anti‐inflammatory drug use, HRs were 1.62 (95% confidence interval (CI) = 1.04–2.52, P = .03) in the highest quartile of total WBC and 2.19 (95% CI = 1.41–3.39, P < .001) in the highest quartile of neutrophil counts. Significant associations were also seen for thromboembolic but not for hemorrhagic strokes. No significant associations were found between lymphocyte or monocyte counts and incident stroke or subtypes. Conclusion: In elderly Japanese‐American men, higher total WBC and neutrophil counts were independent predictors of overall stroke, as well as thromboembolic stroke.